Rare case of clear cell renal cell carcinoma presenting as a unilateral tonsil lesion. Issue 12 (10th December 2020) - Ellis, Shawn David; Meikle, Alison; Al-Salti, Wassim; Sinclair, Georges
Abstract : A 70-year-old man presented with gradually worsening throat discomfort. He had no prior diagnosis of cancer and no travel history of note. Examination revealed a right-sided painless neck lump. He underwent an MRI of the neck, revealing a gadolinium-enhancing tonsillar mass and two brain lesions. Biopsy of the tonsil lesion was in keeping with an epithelial neoplasm, suggesting metastatic renal cell carcinoma. This was confirmed following a staging CT, which revealed a left renal mass and lung metastases. Due to his brain metastases, the patient has been started on the tyrosine kinase inhibitor cabozantinib. A brief discussion on the diagnostic evaluation of a tonsil mass as a rare presentation of renal cell cancer follows this report.